Rozwiąż nierówność 3x do kwadratu > 8x+3

Rozwiązanie

3x kwadrat > 8x+3
3x kwadrat - 8x-3 > 0
delta= b kwadrat + 4*a*c
delta= -8 kwadrat + 4 *3*-3
delta=64-36
delta=28
pierwiastek z delty = pierwiastek z 28
x1 = (8 + pierwiastek z 28):(6)
x2 = (-8 + pierwiastek z 28):(6)
3x²>8x+3
3x²-8x-3>0
a=3 b=-8 c=-3
Δ=b²-4ac
Δ=(-8)²-4×3×(-3)
Δ=64+36
Δ=100
√Δ=10
x₁,₂=
-b ± √Δ
= -
2a
x₁,₂=
8±10
= - = x₁=3 x₂=-1/3
6
i pod parabolą zapisz :
×∈(-∞;-1/3) U (3;+∞)
3x kwadrat > 8x+3 3x kwadrat - 8x-3 > 0 delta= b kwadrat + 4*a*c delta= -8 kwadrat + 4 *3*-3

PODOBNE ZADANIA: